Решите Уровнение (x-1)(x+2) - x(x + 3) = 3x - 1
Решите Уровнение (x-1)(x+2) - x(x + 3) = 3x - 1
Ответ(ы) на вопрос:
1. Раскрываем скобки
[latex] x^{2} + 2x - x - 2 - x^{2} - 3x=3x - 1[/latex]
2. Переносим
[latex] x^{2} + 2x -x -2 - x^{2} - 3x - 3x + 1 = 0[/latex]
3. Находим подобные
[latex]-5x - 1= 0[/latex]
4. Переносим 1
[latex]-5x=1[/latex]
5. У нас получается так:
[latex]-x= \frac{1}{5} [/latex]
6. Умножаем на -1 чтоб -x исчез...
[latex]x=- \frac{1}{5} [/latex]
Ответ: x=[latex] -\frac{1}{5} [/latex]
x^2+2x-x-2-x^2-3x-3x+1=0
-5x-1=0
-5x=1
x=-0,2
Не нашли ответ?
Похожие вопросы